REMOTE LEARNING IMPLEMENTED BY BIPA TEACHERS DURING COVID-19 PANDEMIC - Tri Indri Hardini; Sri Setyarini; Sri Harto (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This research aimed to describe how BIPA teachers implemented remote learning process, identify the problems encountered during COVID-19 pandemic, and explore how Indonesian cultural elements were introduced to students of primary and secondary schools. This research applied a case study design involving eight BIPA teachers in Victoria, Australia as participants. The data were collected through survey questionnaire, virtual interviews, and document analysis. The research data were analysed by making data categories regarding the implementation of remote learning, identification of its problems, and the introduction of Indonesian cultures to students. Interpretation of research findings was done by using relevant theoretical framework. The research findings indicated that the BIPA teachers implemented the remote learning through providing a learning model, listening to students’ individual reading practices, doing a discussion with the students, and implementing simple practices on the selected materials. One of the problems encountered was about students’ motivation. The elements of Indonesian cultures were introduced through identifying its types, describing the identified types of cultures, and writing short essays on the selected cultural topics.